TAFSIR ILMI DAN FENOMENA BIOLOGIS: MENGUAK FUNGSI PENCIPTAAN ANGIN STUDI ANALISIS TAFSIR AL JAWAHIR FI TAFSIR AL-QUR’AN AL KARIM - Lulu Alfina; Khairussalam Khairussalam; Hofifah Hofifah; Siti Hudaroh; Ani Indrawati; Andi Rosa (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Wind is a natural phenomenon involving the movement of air caused by differences in atmospheric pressure. In the interpretation of Al-Jawahir by Tanthawi Jauhari, wind is understood as a sign of Allah's greatness, with significant biological and ecological functions, such as facilitating rainfall, plant pollination, and energy distribution. This study employs a literature review method with a qualitative approach to analyze the functions of wind based on Qur'anic verses and scientific exegesis. The findings reveal that the Qur'an uses the term "al-riyāh" for mercy and "al-rīh" for punishment, highlighting its multifaceted role in supporting ecosystem balance and sustaining life. Tanthawi Jauhari's scientific interpretation emphasizes the importance of wind in natural processes such as bird migration, irrigation, and pollination, demonstrating the harmonious relationship between Qur'anic teachings and modern science. This article underscores that wind not only serves as a blessing for humanity but also as a reminder of Allah's sovereignty in governing the universe.